AUTOMOTIVE TERMINOLOGY FORMATION OF UZBEK AND ENGLISH LANGUAGES - Parpiyeva, U. (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the structural analysis and description of the derivative method of the formation of Uzbek and English automotive terminology.Comprehensive study of the English nomenclature of automotive has not nonetheless been disbursed inside the framework of the term of conduct and theory by Uzbek and English, and linguistic description of the structural and linguistics specificity of the English terms of automotive has not been disbursed. Previously, the laws of the formation and development of this nomenclature inside a similar language haven’t been studied, which might create it potential to predict ways in which of its any development. The nomenclature of the indicated skilled activity isn’t sufficiently studied from the linguistics purpose of read, therefore, the thought and analysis of English terms and also the Uzbek terms of road transport looks relevant.